Rhinosporidiosis in a dog from Uruguay and review of the literature - Borteiro, Claudio; Etcheverze, Javier; León, Natalia de; Nieto, Carina; Arleo, Mailén; Debat, Claudio Martínez; Kolenc, Francisco; Ubilla, Martín; Freire, Jorge; Dutra, Fernando (Brazilian Journal of Veterinary Pathology, 2018)
We report a case of nasal rhinosporidiosis in a dog native to Uruguay, being the sixth report of Rhinosporidium seeberi infection in this host from South America. Diagnosis was made by histopathology of biopsied tissue and specific PCR assay from nasal swab material. The patient was a 3-year-old male dog, of the Dogo Argentino breed, living in a rural area in southeastern Uruguay. An account of published cases in dogs worldwide is provided. As seen in other hosts, male dogs seem to present a predisposition for acquiring the disease.